From Doha to the Next Bretton Woods : A New Multilateral Trade Agenda - Mattoo, Aaditya; Subramanian, Arvind (2012)
Trade problems are an underlying cause of the financial crisis. To truly revive the world economy, a new trade consensus is necessary.